Factors Influencing Students` Pronunciation Mastery at English Department of STKIP PGRI West Sumatera - Ikhsan, Muhammad Khairi (AT-TALIM, 2017)
The research is to find the dominant factors influencing students` pronunciation mastery at English department of STKIP PGRI West Sumatera. This research is using qualitative research method. Total of participants are 10 English students academic year 2016/2017 in English Department of STKIP PGRI West Sumatera who are getting the best mark in pronunciation class. Sample of the research was selected by using purposive sampling technique. The instrument of the research is interview. The purpose of the interview is to get the real arguments about factor influencing students` pronunciation mastery. This research revealed that motivation is the dominant factor influencing students` pronunciation mastery. Most of the students were motivated to increase their pronunciation because they were motivated by native speakers-watching the western or English movies and songs. Besides, they also argued that they wanted to go to overseas so, they should produce the word with correctly pronounced to avoid misunderstanding for both speaker. Based on the data obtained, it can be stated that motivation is the dominant factor influencing students` pronunciation mastery in academic year 2016/2017 at English Department of STKIP PGRI West Sumatera.